2014
DOI: 10.1007/s11136-014-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical behaviour in clinical practice: a multidimensional Rasch analysis from a survey of primary health care professionals of Barcelona (Catalonia, Spain)

Abstract: Paternalistic behaviour persists in PHC. Lesser endorsement of items suggests that patient-centred care and patient autonomy are not fully considered by professionals. Ethical sensitivity could improve if patients are cared for by multidisciplinary teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
10
0
5
Order By: Relevance
“…Testing the information function scale of five response categories and the scale of four response categories is to find out which scale provides a lot of information (Gonza et al, 2014).A detailed description can be seen in Figure 3 below:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Testing the information function scale of five response categories and the scale of four response categories is to find out which scale provides a lot of information (Gonza et al, 2014).A detailed description can be seen in Figure 3 below:…”
Section: Resultsmentioning
confidence: 99%
“…The results of analysis of the scale of five and four response categories can be seen in the following Table 6. Testing on 43 items of the ELVI instrument using the scale of five response categories resulted in 39 fit items with 907 fit persons, while the use of scale of four response categories produced 37 fit items with 976 fit persons.The functioning of response categories in the scale used can be seen through the Andrich threshold parameter (Gonza et al, 2014;Meiser, 2017).Comparison of threshold results responding to the existence of one of the response categories that is effectively used in measuring the ELVI instrument (Andrich, 2011).The results in Table 6 show the Andrich threshold value of the scale of five response categories moving from negative (-) towards positive direction, namely: (-2.17, -0.38, 0.59, to 1.97), while on a scale of four response categories moves from the values (-2.48, 0.33, to 2.14).The estimated threshold value on the scale of the four response categories runs higher than in the scale of the five response categories. This is consistent with the opinions of (McDonald, Vidacovich, Ascione, Williams, & Green, 2015) that the higher the estimated threshold parameters, the greater the disability measured.It was concluded that the scale of the five response categories with estimated threshold parameter values, for each item assessing the effectiveness of the rating scale in measuring ELVI instruments (Gonza et al, 2014).…”
Section: Figure 3 the Informational Function Scale Of Five And Four Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, national (27)(28) and international (19,(29)(30) studies reveal the continuous and epistemological teaching of Ethics and Bioethics as the best way to answer, deliberate and analyze deeply, critically and argumentatively the ethical and bioethical problems, considering, above all, the moral conduct and the ethical-professional obligations.…”
Section: Discussionmentioning
confidence: 99%